A Blind Eye to Industry-Level Corruption? The Risk of Favouring Domestic Industries in the EU ETS. Issue 2 (April 2014) - Brandt, Urs Steiner; Svendsen, Gert Tinggaard
We investigate the risk of favouring domestic industries in the current European Union Emission Trading System (EU ETS). As the EU forms a weak federal structure compared to the US, there is a risk that single countries may free ride on the others by choosing to take a blind eye to industry-level corruption when tempted to favour their own industries. In other words, the optimal level of national cheating may not take into account the external cost it imposes upon other countries and the risk of wide-scale cheating and the possibility of an EU ETS collapse. Such national incentives to cheat correspond to a well-known transnational externality problem from international environmental problems and multiplayer prisoners' dilemma games. Thus, there is a strong need for systematic empirical analysis of whether cheating actually occurs in the EU ETS as predicted by theory.